Sejarah dan Perkembangan Pesantren Modern Ummul Quro Al-Islami Bogor - Agus Ali; Nurwadjah Ahmad EQ; Andewi Suhartini (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2022)
This article aims to discuss the history and development of the modern Islamic boarding school Ummul Quro Al-Islami Bogor including: history, founder profile, goals, vision and mission. By using a descriptive qualitative method. Based on the results of research on integrated curriculum management at the Modern Islamic Boarding School Ummul Quro Al-Islami, it can be concluded as follows: (1) The history of the modern Islamic boarding school Ummul Quro Al-Islami Bogor was founded by KH. Helmi Abdul Mubin, Lc with a capital of 250 thousand rupiah, was motivated by the arrival of a delegation from Australia to the Islamic boarding school where he taught to find an ustadz who was good at English to teach religion in the Australian Muslim community (2) KH. Helmi Abdul Mubin, Lc as the founder of the modern Islamic boarding school Ummul Quro Al-Islami Bogor is a Madurese son born on March 23, 1956, the first of four children of the late Abdul Mubin and Musyaroh, who spent his childhood in Prenduan Madura, after graduating from Pragaan Elementary School in Sumenep last continued his education at the modern Gontor boarding school in Ponorogo, East Java. (3) The purpose of establishing the modern Islamic boarding school Ummul Quro Al-Islami Bogor is to participate in building a just and prosperous society and republic of Indonesia and receive the pleasure of Allah SWT, forming a generation of Muslims who excel in academic and non-academic achievements as a provision to continue to higher education. and or live independently, produce a generation of Muslims who are polite in speech and behavior, create a generation of Islam with a social spirit (serving the community) and grow a generation of Muslims who are diligent in carrying out mandatory and sunnah worship based on the understanding of ahlussunnah wal jama'ah. The vision of the modern Islamic boarding school Ummul Quro Al-Islami Bogor is the realization of a generation of Muslims who excel in achievement, have noble character, do good deeds and diligently worship according to the teachings of Islam Ahl as-Sunnah wa al-jama'ah, as for the mission of the modern Islamic boarding school Ummul Quro Al-Islami Bogor namely providing quality education in achieving academic and non-academic achievements, preparing cadres of ulama and community leaders who are mutafaqqih fi ad-diin with the understanding of Ahl as-Sunnah wa al-jama'ah, preparing competent Islamic generations (science, skills, social behavior, sincere faith) to take part in the international world and educate generations of Islam who are obedient to Allah and His Messenger and have a sense of responsibility towards themselves, their family, society and country. Keyword: History, Development and Modern Islamic Boarding School